BANK POTENTIAL AS A CRIME MEANS THROUGH FINANCIAL TRANSACTION - Johannes Ibrahim Kosasih (Fakultas Hukum, Universitas Warmadewa, 2018)
The ease of transactions through bank financial institutions increasingly perceived by the entire nation with the development of sophisticated technology that allows it to be completed in a short time. Technological sophistication in the variety of bank services is utilized by various parties as a means to commit various crimes. Crimes involving banks as a means of criminal banking and criminal offenses in the banking sector. This paper reveals various cases in the field of banking with legal juridical normative review by describing several cases that have been processed by law. The specific objective is to examine the bank's potentials to become a vehicle for crime from the point of view and rule of law of Indonesia. To achieve this goal, in the design of the study, conceptual and statute approaches to legislation are used by collecting and reviewing banking laws. The main data were obtained from the field, namely in the form of criminal cases that have been processed through law. The results of data analysis show that banking crime and criminal offense in banking involves banks as a means of crime. This has a tremendous negative impact for the country that is making a loss in the field of Indonesian economy. For that, steps to revise or amend the regulation on banking is urgently required because ternya he has a significant deficiency. Banks as trust agencies should have strict security in preventing any opportunity to commit crimes.